(untitled) (Teacher’s World: Journal of Education and Research, 2024)
In Bangladesh, government-led initiatives in inclusive education aim to integrate individuals with disabilities into mainstream educational settings. Recognizing the significant influence of peers, this study examines the perceptions of University of Dhaka students towards their peers with disabilities. Participants from various departments offer insights into their perceptions and justifications regarding individuals with disabilities. Through a survey questionnaire administered to 105 students, the research explores perceptions, beliefs, and intentions towards peers with disabilities. The findings highlight a predominantly positive attitude among both undergraduate and postgraduate students, emphasizing the importance of inclusive practices within higher education. This study enhances the understanding of peer interactions and perceptions towards disability in an academic context, stressing the necessity of fostering inclusive environments that encourage diversity and acceptance among students. Further research could build upon these findings to inform policies and practices aimed at improving inclusivity and support for students with disabilities in higher education. Teacher’s World: Journal of Education and Res arch, 50(1): 171-186